The Anti-tumoral Efficacy of a Docetaxel-loaded Liposomal Drug Delivery System Modified with Transferrin for Ovarian Cancer - Yuan, M. Q.; Zhu, F.; Lou, J. Y.; Yuan, W. M.; Fu, L.; Liu, S.; Zhang, Z. Z.; Liu, C. Y.; He, Q. (Drug Research, 2014)
To reduce the toxic effect on normal cells and improve the treatment effects of docetaxel, a novel transferrin modified docetaxel-loaded long circulating liposome for ovarian tumor was established for the first time. The transferrin-modified long-circulating liposomes loaded with docetaxel (TF-LP-DOC) were prepared by the post-insertion method and exhibited excellent characteristics in terms of particle size, encapsulation efficiency and stability. We investigated the targeting efficiencies of liposomes by the cellular uptake in vitro and biodistribution in vivo, and identified the therapeutic effects using cytotoxicity experiment (in vitro)and tumor growth inhibition (in vivo) on ovarian cancer. The in vitro and in vivo results showed that TF-LP-DOC were successfully established and presented an enhanced targeting ability. With decreased side effect and improved anti-tumor efficacy of chemotherapeutic drugs, TF-LP-DOC proved itself to be a very promising tumor targeted drug delivery system.
Keywords: transferrin; long-circulating liposome; docetaxel; ovarian tumor